Canva-Based Digital Media Development with an Inquiry Approach to Improve Conceptual Understanding and Critical Thinking - Purnomo, Dian; Mimi Hariyani (Journal of Practice Learning and Educational Development, 2026)
The limitations of interactive learning media that are able to stimulate students' active involvement in Physics learning are still a challenge in many educational units. As a result, students tend to have difficulty understanding concepts and developing critical thinking skills. This research aims to develop Canva-based digital media that is integrated in an inquiry-based learning model, in order to improve students' understanding of concepts and critical thinking skills on Quantity and Unit materials. This research uses the Research and Development (R&D) method with a 4D development model approach (Define, Design, Develop, and Disseminate). The research subjects were grade VII MTs students. Data collection techniques included interviews, expert validation questionnaires, student assessment questionnaires on the media, and practicality questionnaires. Data were analyzed descriptively, quantitatively, and qualitatively. The results of expert validation showed that the media met the valid criteria with an average score of 83.3% in terms of content, 93.8% in language, and 100% in graphic design, as well as a reliability value of 0.861 in the instrument. Students' assessments of the product showed an average score of 3.27 on a scale of 4 (good category) with Cronbach's Alpha of 0.957. The practicality test resulted in an average score of 3.18 (good category) with a reliability value of 0.944. All of these findings show that the developed media is not only feasible and practical to use, but also effective in supporting inquiry-based learning activities. In conclusion, Canva-based learning media with an inquiry approach is declared valid, practical, and effective in improving students' understanding of concepts and critical thinking. This medium can be an innovative alternative in physics learning that is interactive, visual, and in accordance with the demands of 21st century learning.